2009
DOI: 10.1590/s0101-20612009000400001
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da bebida de café descascado sobre a atividade antioxidante, os parâmetros hematológicos e bioquímicos em ratos

Abstract: The aim of this study was to verify the effect of filtered coffee brew prepared with peeled Coffea arabica on the lipid peroxidation and on hematological and biochemical parameters in vivo. Rats were ingested 280 mg/kg/day of coffee brew for 7 days (acute treatment) and 30 days (chronic treatment). In order to determine whether coffee can reduce the oxidative stress, the rats brain isolated lipid peroxidation was accessed evaluating the thiobarbituric acid-reactive substances (TBARs).The ingestion of coffee br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(40 reference statements)
4
5
0
1
Order By: Relevance
“…Recent studies have shown that coffee intake in the form of an infusion decreased levels of lipidic peroxidation [29], and other experiments with rats show data similar to the present study (i.e., an increase in the antioxidant levels after administration of coffee extract from a carcinogen with Nmethylpyridinium-2-aldoxime and carbon tetrachloride) [26,30]. In addition to oxidative stress in the liver, biochemical parameters were analyzed in serum.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Recent studies have shown that coffee intake in the form of an infusion decreased levels of lipidic peroxidation [29], and other experiments with rats show data similar to the present study (i.e., an increase in the antioxidant levels after administration of coffee extract from a carcinogen with Nmethylpyridinium-2-aldoxime and carbon tetrachloride) [26,30]. In addition to oxidative stress in the liver, biochemical parameters were analyzed in serum.…”
Section: Resultssupporting
confidence: 85%
“…We observed that neither coffee nor DMH produced modifications of the biochemical parameters of serum levels (p< 0. [29], which confirmed the ability of coffee to reduce some parameters such as triglycerides and cholesterol. The interception of free radicals generated in the cellular metabolism by the bioactive compounds (as observed in the analyses of MDA), suggests that coffee may act as antimutagenic or anticarcinogenic; however, the roles of these bioactive compounds have not been well defined in process of the carcinogenesis [8,22,23].…”
Section: Resultssupporting
confidence: 59%
“…Thus, when compared with these extracts, we see that even a low concentration of the aqueous acetone extract of jatoba had a high antioxidant potential in vivo (Duarte et al, 2009); (Dyedemi et al, 2010).…”
Section: Resultsmentioning
confidence: 81%
“…In a study on coffee (Coffea arabica), Duarte et al (2009) found 48.60% inhibition of lipid peroxidation in Wistar rats with acute treatment for 7 days and 53.40% with chronic treatment (30 days). Regarding the time of administration, the aqueous acetone extract of jatobá was more effective at inhibiting lipid peroxidation at a concentration of 500 µL/day, causing 62.92% inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Many articles available in several bases of research (Gonçalves et al, 2007;Lima et al, 2008;Duarte et al 2009;Messias et al, 2010;Melo et al, 2012;Taiwo Idowu et al, 2013;Achuba;Ogwumu, 2014;Lima et al, 2014;Mulata et al, 2015) show that it is still common the use counters to determine the blood cell count in animals, however, many of them correspond to standard equipment for human blood and not for laboratory animals. In this context, rodents are the most used animals for scientific studies in several areas as they have similar genetic and physiological characteristics to humans (Harkness;Wagner, 1993;Cubas et al, 2007, Melo et al, 2012Lima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%